Role of Endoplasmic Reticulum Aminopeptidases in Health and Disease: from Infection to Cancer - Doriana Fruci (International Journal of Molecular Sciences, 2012)
Endoplasmic reticulum (ER) aminopeptidases ERAP1 and ERAP2 (ERAPs) are essential for the maturation of a wide spectrum of proteins involved in various biological processes. In the ER, these enzymes work in concert to trim peptides for presentation on MHC class I molecules. Loss of ERAPs function substantially alters the repertoire of peptides presented by MHC class I molecules, critically affecting recognition of both NK and CD8+ T cells. In addition, these enzymes are involved in the modulation of inflammatory responses by promoting the shedding of several cytokine receptors, and in the regulation of both blood pressure and angiogenesis. Recent genome-wide association studies have identified common variants of ERAP1 and ERAP2 linked to several human diseases, ranging from viral infections to autoimmunity and cancer. More recently, inhibition of ER peptide trimming has been shown to play a key role in stimulating innate and adaptive anti-tumor immune responses, suggesting that inhibition of ERAPs might be exploited for the establishment of innovative therapeutic approaches against cancer. This review summarizes data currently available for ERAP enzymes in ER peptide trimming and in other immunological and non-immunological functions, paying attention to the emerging role played by these enzymes in human diseases.